Pertanggungjawaban Pidana Korporasi atas Kerusakan Lingkungan yang Mengakibatkan Bencana Banjir Bandang berdasarkan Undang-Undang Perlindungan dan Pengelolaan Lingkungan Hidup - Roby Andika Harahap; Tri Reni Novita (Jembatan Hukum : Kajian ilmu Hukum, Sosial dan Administrasi Negara, 2026)
The flash flood disaster that hit Indonesia, including the devastating disaster in three Sumatran provinces in November-December 2025 which resulted in more than 900 casualties and trillions of rupiah in losses, shows a strong correlation between environmental damage caused by corporate activities and increased disaster risk. The purpose of this study is to analyze corporate criminal liability for environmental damage resulting in flash flood disasters based on the Environmental Management Law (UU PPLH), examine the mechanism for proving corporate criminal liability, and evaluate the application of criminal sanctions against corporations that commit environmental damage resulting in flash flood disasters. The research method used is normative legal research with a descriptive analytical statute approach. Data collection techniques are carried out through library research and interviews with sources at the North Sumatra Provincial Environmental Service. The data obtained were analyzed qualitatively. The results of the study indicate that: First, corporate criminal liability for environmental damage resulting in flash floods has been comprehensively regulated in Articles 116 to 120 of the Environmental Management and Management Law, which recognizes corporations as subjects of criminal law and regulates the criteria for corporate crimes (committed by, for, or on behalf of a business entity), the responsible party (the business entity and/or the person giving the order/leader of the activity), a one-third aggravation of the sentence, and corporate representation in court, as reinforced by Supreme Court Regulation Number 13 of 2016. The conclusion of this study is that the Environmental Management and Management Law has provided a comprehensive legal framework for corporate criminal liability for environmental damage resulting in flash floods. However, the effectiveness of law enforcement still needs to be improved through accelerating the judicial process, strengthening the capacity of law enforcement, improving inter-agency coordination, and strengthening the decision execution mechanism.